83.3k views
2 votes
Which is the correct way to solve the given equation

Which is the correct way to solve the given equation-example-1

1 Answer

3 votes

Option 2.
x = \frac{4 \pm \sqrt{(-4)^(2)-4 (1)(-21)}}{2 (1)} shows the correct way to use the quadratic formula to solve the given equation.

Explanation:

Step 1:

For an equation of the form
ax^(2) +bx+c=0 the solution is
x=\frac{-b \pm \sqrt{b^(2)-4 a c}}{2 a}.

Here a is the coefficient of
x^(2), b is the coefficient of x and c is the constant term.


x^(2) -4x=21 can also be written as
x^(2) -4x-21=0.

Comparing
x^(2) -4x-21=0 with
ax^(2) +bx+c=0, we get that a is 1, b is -4 and c is -21.

To get the solution, we substitute the values of a, b, and c in
x=\frac{-b \pm \sqrt{b^(2)-4 a c}}{2 a}.

Step 2:

Substituting the values, we get


x=\frac{-b \pm \sqrt{b^(2)-4 a c}}{2 a}= \frac{-(-4) \pm \sqrt{(-4)^(2)-4 (1)(-21)}}{2 (1)}.


\frac{-(-4) \pm \sqrt{(-4)^(2)-4 (1)(-21)}}{2 (1)} = \frac{4 \pm \sqrt{(-4)^(2)-4 (1)(-21)}}{2 (1)}.

This is option 2.

User MystikSpiral
by
5.4k points